2012
DOI: 10.1002/cbic.201200023
|View full text |Cite
|
Sign up to set email alerts
|

Who's Who? Allocation of Carbonyl Reductase Isoenzymes from Candida parapsilosis by Combining Bio‐ and Computational Chemistry

Abstract: Proof of identity: The previously described ability of Candida parapsilosis lysate to reduce structurally diverse ketones led to the discovery of two carbonyl reductases as possible candidates for this interesting biotransformation. Homology modelling and prediction of indicator substrates helped to identify which enzyme has the large substrate scope verified by biochemical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The enzymew as first described, purified, andc haracterizedb yP eters and co-workers. [11] Thereby,itwas demonstrated that the enzyme preparation used previously actually consisted of two different ADHs, CPCR1 and CPCR2, the latter being mainly responsible for the broad substrate spectrum described in previouss tudies. [11] Thereby,itwas demonstrated that the enzyme preparation used previously actually consisted of two different ADHs, CPCR1 and CPCR2, the latter being mainly responsible for the broad substrate spectrum described in previouss tudies.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The enzymew as first described, purified, andc haracterizedb yP eters and co-workers. [11] Thereby,itwas demonstrated that the enzyme preparation used previously actually consisted of two different ADHs, CPCR1 and CPCR2, the latter being mainly responsible for the broad substrate spectrum described in previouss tudies. [11] Thereby,itwas demonstrated that the enzyme preparation used previously actually consisted of two different ADHs, CPCR1 and CPCR2, the latter being mainly responsible for the broad substrate spectrum described in previouss tudies.…”
Section: Introductionmentioning
confidence: 80%
“…[3b, [6][7] Later,t he enzymew as genetically located, cloned, and expressed in Escherichia coli. [11] Thereby,itwas demonstrated that the enzyme preparation used previously actually consisted of two different ADHs, CPCR1 and CPCR2, the latter being mainly responsible for the broad substrate spectrum described in previouss tudies. It became obvious that the same enzyme had independently been described and applied under ad ifferent name before.…”
Section: Introductionmentioning
confidence: 80%
“…The likeability of the latter has for example been demonstrated for the carbonyl reductase activity of Candida parapsilosis described by Kula and coworkers in 1995 [20]. Only in 2011 it became clear, that the CPCR preparation actually contained two enzymes where one is mainly responsible for the characteristics that were initially described [21].…”
Section: Kred-activity Of Scleroderma Citrinummentioning
confidence: 88%
“…19 Such silicones are mostly generated by the treatment of “standard” silicone with UV/ozone20 or plasma discharge followed by silanization21 or by incorporation of hydrophilic moieties into the matrix 22. A simple method for the incorporation of hydrophilic compounds involves vinylic groups because these enable direct cross‐linking during hydrosilylation,23 although this requires preliminary modification of the hydrophilic components 24…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilization of silicone for the preparation of silCoat biocatalysts was performed with carbonyl reductase from Candida parapsilosis (CPCR2)24 as a model enzyme and poly(ethylene glycol) (PEG) as an environmentally benign and enzyme‐friendly hydrophilizer 23. 25–27 CPCR2 is a synthetically interesting enzyme owing to its broad substrate range and high enantioselectivity26 requiring a distinctly aqueous environment for appropriate activity.…”
Section: Introductionmentioning
confidence: 99%